Pemanfaatan Media Sosial Tiktok sebagai Forum Kreativitas dan Sarana Literasi Digital - Nia Maulida (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
A person's daily life can be influenced by culture, creativity, communication patterns, and the information they get due to the use of social media. TikTok is one of the many applications used and popular today, especially among teenagers. TikTok social media can also be utilised as a creativity forum and digital literacy tool. People need a forum that can be used to channel creativity as well as being a motivation and encouragement for users to channel their thoughts and ideas to the Tiktok platform. Because in this era there is still a lack of applications that can be used as a creativity forum. In addition, the lack of literacy at this time can be a problem that must be faced. The lack of literacy, especially digital literacy, can make social media users continue to accept any information without accepting that the information is true or contains a lie. The existence of Tiktok social media can be used as a means of digital literacy. Besides containing entertainment, Tiktok also contains information that its users need.